PENDIDIKAN AGAMA KRISTEN DALAM LINGKUNGAN PEMBELAJARAN EFEKTIF DI MASA PANDEMI COVID-19 - Charis Vita Juniarty Boangmanalu; Valentino Reykliv Mokalu (SOSIOEDUKASI, 2022)
Effective learning during the Covid-19 pandemic can be done if you apply interesting and active learning methods for educators and students. Educational institutions in the distance learning process can leave the old learning culture, and are expected to be able to face learning with a new culture. In facing this new culture, educators can present alternative educational processes. This article seeks to offer creative ways not only on the platform used, but also regarding learning times, methods, and approaches to students during the Covid-19 Pandemic Period. The research method used in this research is library research by collecting library data. The results of the study show that effective learning during the Covid-19 pandemic can be carried out if you apply interesting and active learning methods for educators and students. In addition, educational institutions in the distance learning process are able to leave the old learning culture, and are expected to be able to face learning with a new culture. By applying creative ways, it is not only the platform used, but also about learning time, methods, and approaches to students. This perspective encourages educational institutions to continue to work in facilitating and paying attention to various methods and approaches needed by students and educators.